2008
DOI: 10.1108/17530180200800027
|View full text |Cite
|
Sign up to set email alerts
|

Transition and social networks of young people with learning disabilities

Abstract: School leavers with learning disabilities are often lost within service structures as part of the transition process. Many young people lose their social networks at the point of transition to adulthood. This paper provides an insight into the views and aspirations of young people, and highlights the importance of social networks in promoting the psychological well‐being of young people with learning disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…It has been suggested that this issue is particularly common among young people with an intellectual disability [1,34]. Our qualitative data included issues related to maintaining social contact and the ability to make friends after they had left school as well as the level of acceptance for the young person within their community.…”
Section: Individual Levelmentioning
confidence: 99%
“…It has been suggested that this issue is particularly common among young people with an intellectual disability [1,34]. Our qualitative data included issues related to maintaining social contact and the ability to make friends after they had left school as well as the level of acceptance for the young person within their community.…”
Section: Individual Levelmentioning
confidence: 99%
“…). Transition planning is often marked by low levels of inclusion of relevant stakeholders (Kaehne ), little choice for young people and their families (Raghavan & Pawson ; Kaehne ), and a predominance of pathways that suit services rather than users and carers (Wagner et al . ; Heslop & Abbott ).…”
Section: Introductionmentioning
confidence: 99%
“…Transition for young people with ID has received much attention from policy makers and researchers in the last two decades, but transition outcomes for this population remain poor (While et al 2004;Grant & Ramcharan 2007;Grigal et al 2011). Transition planning is often marked by low levels of inclusion of relevant stakeholders (Kaehne 2010), little choice for young people and their families (Raghavan & Pawson 2008;Kaehne 2009), and a predominance of pathways that suit services rather than users and carers (Wagner et al 2006;Heslop & Abbott 2007).…”
mentioning
confidence: 99%
“…Transition is a multifaceted process that affects not only young people leaving school. Transitions occur throughout the life course of every person, with or without disabilities, and take various forms, ranging from biological and social change to change in vocational and educational context (Barry, 2001a; 2001b; Blacher, 2001; Catan, 2004; Cote, 2000; Jordan & Dunlap, 2001; Mittler, 2007; Pole, Pilcher, & Williams, 2005; Raghavan & Pawson, 2008; Shepperdson, 2000). For young people with intellectual disabilities, transition is defined in a narrow sense through the statutory framework set out in the Code of Practice (Department for Education and Skills, 2001) and the Education Act (Beyer, 2005).…”
Section: Introductionmentioning
confidence: 99%